The Effects of Pass Number and Die Channel Angle of Equal Channel Angular Pressing on Innovative Magnesium Composite Material - Xin Zhang; Jian Han; Jing Tian; Lisong Zhu; Peng Zhang; Yue Wang; Zhengyi Jiang (Metals)
The effects of the designed equal channel angular pressing (ECAP) procedures on microstructures, mechanical properties and corrosion resistances of newly developed nano-MgO/Mg–Zn–Ca composite materials have been investigated in this study. The die channel angles selected by the ECAP processes are 90°and 120°, and the corresponding composite materials are kept for 15 min in the ECAP mold at 300 °C before 1, 4, and 8 passes through route<semantics> BC</semantics>. It can be understood that the sizes of grains and second phases were significantly reduced because of continuous dynamic recrystallization (C-DRX) and mechanical shearing, and the ECAP process with the die angle of 90° shows more evidence of grain refinement owing to the higher shear stress. The obtained mechanical properties stipulated that both the yield and ultimate strength were improved after ECAP, which is related to the interaction of grain and texture evolution, while the elongation increases drastically from 14% (as-extruded state) to 34% (ECAP-ed state). Meanwhile, the improvement of corrosion resistance by microstructural evolution is more significant than adverse effects originating from the internal defects of the material itself as well as the defects originating from the number of passes. Ultimately, the conclusions were made based on the results regarding performance improvement by the optimized parameters designed and utilized in ECAP for this novel Mg composite material.